Children Consider Procedures, Outcomes, and Emotions When Judging the Fairness of Inequality - Stowe, Lucy M.; Peretz-Lange, Rebecca; Blake, Peter R. (Frontiers in Psychology, 2022)
Children tend to view equal resource distributions as more fair than unequal ones, but will sometimes view even unequal distributions as fair. However, less is known about how children form judgments about inequality when different procedures are used. In the present study, we investigated children’s consideration of procedures (i.e., resource-distributing processes), outcomes (i.e., the distributions themselves), and emotions (i.e., the emotional reactions of those receiving the resources) when judging the fairness of unequal resource distributions. Participants (N = 130, 3- to 8-year-olds) were introduced to a Fair Coin (different color on each side) and an Unfair Coin (same color on both sides). In two between-subjects conditions, they watched a researcher flip either the Fair or Unfair coin in order to distribute resources unequally between two child recipients. Participants then rated the fairness of this event, provided verbal justifications for their ratings (coded for references to procedures and/or outcomes), and rated the emotional state of each recipient (from which an Emotion Difference Score was computed). Results revealed that participants rated the event as more fair in the Fair Coin than the Unfair Coin condition. References to the outcome in children’s justifications predicted lower fairness ratings, while references to the procedure only predicted lower ratings in the Unfair Coin condition. Greater Emotion Difference Scores predicted lower fairness ratings, and this effect increased with age. Together, these results show that children consider procedures, outcomes, and emotions when judging the fairness of inequality. Moreover, results suggest age-related increases in consideration of recipients’ emotions makes inequality seem less fair, even when fair procedures are used. Implications for the development of fairness are discussed.